The role of protein and amino acids in sustaining and enhancing performance (National Academy Press, 1999)
It is a commonly held belief that athletes, particularly body builders, have greater requirements for dietary protein than sedentary individuals. However, the evidence in support of this contention is controversial. This book is the latest in a series of publications designed to inform both civilian and military scientists and personnel about issues related to nutrition and military service. Among the many other stressors they experience, soldiers face unique nutritional demands during combat. Of particular concern is the role that dietary protein might play in controlling muscle mass and strength, response to injury and infection, and cognitive performance. The first part of the book contains the committee's summary of the workshop, responses to the Army's questions, conclusions, and recommendations. The remainder of the book contains papers contributed by speakers at the workshop on such topics as, the effects of aging and hormones on regulation of muscle mass and function, alterations in protein metabolism due to the stress of injury or infection, the role of individual amino acids, the components of proteins, as neurotransmitters, hormones, and modulators of various physiological processes, and the efficacy and safety considerations associated with dietary supplements aimed at enhancing performance.